2021
DOI: 10.2147/ijgm.s288733
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Echocardiographic, and Therapeutic Characteristics of Heart Failure in Patients with Preserved, Mid-Range, and Reduced Ejection Fraction: Future Directions

Abstract: Background Heart failure (HF) is recognized as a worldwide epidemic. Definitions and risk stratification are usually based upon measurements of left ventricular ejection fraction (LVEF) but such classifications reflect an underlying spectrum of different pathologic, phenotypic, and therapeutic patterns. Methods This was a retrospective cohort study of HF patients in Saudi Arabia. Patients were divided into three categories based on LVEF: those with preserved ejection fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…Our study confirms the intermediate character of HFmrEF patients' clinical profile, which is widely described in the literature [6][7][8][9]. The hemodynamic profile of all three groups shared the same characteristics at rest with significant differences exclusively in STR and PEP between HFmrEF and HFrEF patients.…”
Section: Resultssupporting
confidence: 88%
“…Our study confirms the intermediate character of HFmrEF patients' clinical profile, which is widely described in the literature [6][7][8][9]. The hemodynamic profile of all three groups shared the same characteristics at rest with significant differences exclusively in STR and PEP between HFmrEF and HFrEF patients.…”
Section: Resultssupporting
confidence: 88%
“…Moreover, in a retrospective cohort study on HF patients in the Eastern region of Saudi Arabia, the majority of HF patients were males, and the mean age was 63 years. The most common comorbidities were hypertension and diabetes mellitus as well [ 15 ]. A variety of factors could contribute to this result but mainly it could be explained by the fact that males generally are more prone to cardiac disease as the cardioprotective effect estrogen has on females is well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Another study that included patients from four centers in Riyadh and Buraida similarly reported that the majority of patients were males and that hypertension and diabetes mellitus were the most frequent comorbidities [ 14 ]. Moreover, in a retrospective cohort study on HF patients in the Eastern region, the majority of HF patients were males [ 15 ]. The most common comorbidities were hypertension and diabetes mellitus in the three studies mentioned [ 13 - 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation